Profits plan and cash flow - Pacheco Mexzon, Raimundo Renaun (2015)
When a company produces goods or services must invest funds in working capital waiting for profit. To estimate whether this activity generates profits is necessary to develop the operating budget as a Profits Plan. As Finance Manager responsible for managing efficiently the funds generated by the operations of the company, musts prepare the Cash Flow from Profit Plan. Therefore it is objective of this article submit how prepare the Cash Flow from a Profits Plan.